Uzbek and English political texts: linguocultural features and translation - Ergasheva , Nigora Erkin qizi (The Lingua Spectrum, 2026)
Political discourse is a key site of cultural and ideological meaning-making, and its translation across languages is a demanding task in applied linguistics. This article examines linguocultural features of Uzbek and English political texts, focusing on metaphorical language as a vehicle of ideological framing. Drawing on conceptual metaphor theory, critical discourse analysis, and cross-cultural pragmatics, the study analyzes 60 political speeches and official statements from English- and Uzbek-speaking contexts (2015-2024). Moreover, findings reveal systematic metaphorical differences: English political discourse relies heavily on war, journey, and organism metaphors that foreground competition and individual agency, whereas Uzbek rhetoric favors metaphors from nature, family, and ancestral wisdom that emphasize collectivity and cultural continuity. These differences challenge translators, as surface equivalence often fails to preserve ideological intent or pragmatic function. As well as, the article proposes strategies for culturally informed translation of political metaphor and contributes to non-Western political discourse analysis.